Effort of Satintelkam Political Unit Raising to Realize Security and Order in the Village Head Election in the Jurisdiction of Magelang Polres - Muhammad Habib Kevin (Akademi Kepolisian Republik Indonesia, 2023)
Village Head Election (Pilkades) is a democratic party activity with high vulnerability. In the 2016, 2019, and 2022 elections, there were always kamtibmas disturbances, which raised indicators of problems in pre-emptive efforts, namely in the raising activities of the Satintelkam Political Unit of the Magelang Police. The research method used is a qualitative method that is using descriptive analysis, so that the data collection techniques used are interviews, observation, and document studies. The focus of this research is optimizing the formation of the Satintelkam Political Unit to realize security and order Pilkades in the jurisdiction of the Magelang Police. Primary data was obtained from interviews with members of the Political Unit of the Satintelkam and the Village Consultative Body who are carrying out the Pilkades. Secondary data was obtained through a review of documents related to the object of research. The results showed that the raising of the Satintelkam Political Unit related to the series of Pilkades activities was still not optimal. The implementation of raising by waiting for community reports has not been in accordance with intelligence activities which are a form of pre-emptive efforts.